Assessing the Impact of Nigerian Seaports’ Operational Performance on the Construction Sector’s Contribution to GDP - Ismail Gbolahan Dere; Joel Ademola Ojekunle (CSID Journal of Infrastructure Development)
The construction sector in Nigeria relies heavily on imported materials; however, inefficiencies and frequent delays at the seaports have led to increased costs, significantly affecting the sector’s contribution to the nation’s Gross Domestic Product (GDP). This study examines the relationship between the operational performance of Nigerian seaports and the GDP contribution of the construction sector. Secondary data on GDP and port performance indicators were obtained from the Central Bank of Nigeria (CBN) and the Nigerian Ports Authority (NPA), covering the period from 2011 to 2023. The analysis employed descriptive and inferential statistics methods, including regression and Stochastic Frontier Analysis (SFA). The findings reveal that the key performance indicators such as Cargo Throughput (LnCTHP), Personnel Efficiency (LnP), and Ship Traffic (LnST) significantly and positively influence GDP, with β-values of 0.462, 0.283, and 0.402, respectively (p < 0.05). In contrast, inefficiencies represented by prolonged Turnaround Time (LnTAT) and Waiting Time (LnWT) had negative effects on GDP, with β-values of −0.178 and −0.098, respectively (p < 0.05). Additionally, Gross Registered Tonnage (LnGRT) was found to have a positive influence on GDP (β = 0.213, p = 0.017), highlighting the economic benefit of accommodating larger vessels. The regression model demonstrated strong explanatory power, with an R² of 0.908 and an adjusted R² of 0.882, indicating that the included variables could explain 88.2% of the variance in GDP. These findings are consistent with previous research and highlight the crucial role of port efficiency in driving economic growth. The study recommends focused investments in modern cargo handling technologies, workforce optimization, and infrastructure upgrades to mitigate delays. It also advocates for strategic partnerships with international shipping companies and policy interventions, such as tax incentives for modernization and simplifying customs procedures, to enhance overall efficiency. Future research should further explore the role of port digitalization in facilitating GDP growth. Addressing existing inefficiencies and leveraging operational improvements can support Nigerian seaports in substantially contributing to the construction sector’s GDP, thereby supporting broader sustainable economic development.